Epidemiology and diagnosis of human leptospirosis in Malaysia - Mohamed El-Jalii, Isam Mohamed Ali. (2000., 2000)
Retrospective study of human leptospirosis in Malaysia based on microscopic agglutination test (MAT) showed 13% overall prevalence of infection for the period 1983-1998. Results indicated that the prevalence was decreasing in the last five years (1994-1998). The prevalence was highest among Indians (16.67%) followed by Malays (11.48%) and the least among Chinese (5.88%). The 20-29 year-old group showed the highest prevalence of infection (17.13%). Less than 10 year-old group showed the least prevalence of infection (5.66%). Generally, many of the cases occurred between the ages of 20-50 years. Serological survey based on enzyme-linked immunosorbent assay (ELISA) showed a high overall prevalence (12.56%) of leptospiral infection. Kuala Lumpur showed the highest prevalence (19%) whilst Penang recorded the lowest prevalence (6.67%). No significant differences in the prevalence between the other states was noted. Analysis of leptospiral DNA with restriction enzymes, Hind III, BamH I and EcoR revealed a high heterogeneity between the serovars examined. This high heterogeneity may be due to the large genome of the genus Leptospira. No relationship was found between the restriction patterns and the species from which the isolate was isolated. Similarities were observed among isolates of the same serovar. The 10 leptospiral field isolates were assayed for presence of plasmid DNA. Only two isolates were found to harbor plasmid DNA. The plasmid profiling obtained is of limited epidemiological value for differentiation of leptospiral isolates. It appears that human leptospirosis is an endemic infection in Malaysia. The findings showed that ELISA was a suitable serological test for diagnosis of leptospirosis compared to MAT and IHA tests. On the other hand, the application of PCR and REA in the diagnosis of leptospirosis would be useful.
Thesis (Ph.D.) - Universiti Putra Malaysia, 2000.
Keywords: Leptospirosis -- Malaysia